Nanotechnology for sustainable food packaging - Anandharamakrishnan, C.; Moses, Jeyan A.; Leena, Maria (Wiley, 2025)
Latest techniques for the development of biodegradable food packaging casings with commentary on safety concerns and regulatory frameworks - Nanotechnology for Sustainable Food Packaging covers the latest techniques and applications of nanotechnology, demonstrating capabilities to revolutionize the food packaging sector. This includes concepts of biodegradable food packaging, approaches to improve material functionality, robust sensing systems, and the scope of employing advanced analytical and computational approaches to support progress in the field. Throughout, the text focuses on the United Nations Sustainable Development Goals, including life cycle analysis, biodegradability, green practices, eco-friendliness, and sustainability. Nanotechnology for Sustainable Food Packaging covers the latest techniques and applications of nanotechnology, demonstrating capabilities to revolutionize the food packaging sector. This includes concepts of biodegradable food packaging, approaches to improve material functionality, robust sensing systems, and the scope of employing advanced analytical and computational approaches to support progress in the field. Throughout, the text focuses on the United Nations Sustainable Development Goals, including life cycle analysis, biodegradability, green practices, eco-friendliness, and sustainability. Written by a team of highly qualified authors, Nanotechnology for Sustainable Food Packaging discusses sample topics including: Nanotechnology's potential to improve the shelf life of food products, the chemistry and functionality of different materials based on merits and possible challenges; Sources, chemistry, and functionality of various bio-based sources and their usage as nanocomposites, and bio-based alternatives, drawbacks, and research trends; Bioactive compounds in food packaging and their benefits, preparation methods, characterization approaches, delivery, and assessment; Surface modification approaches through sustainable physico-chemical approaches, and the development of flexible packaging materials suitable for specific requirements such as nonthermal processing. Nanotechnology for Sustainable Food Packaging is an essential scientific and technological reference for scientists and R&D personnel who are interested in advancing food packaging technologies. The book is also valuable for students, researchers, and food industry professionals studying nanotechnology in food, food packaging, and food science and technology. Provided by publisher.
Keywords: Food -- Packaging.; Nanotechnology.; Sustainable development.; elektronické knihy; electronic books